Iterated local search algorithm for the vehicle routing problem with backhauls and soft time windows - Brandão, José (2018)
The vehicle routing problem with backhauls and soft time windows contains two disjoint sets of customers: those that receive goods from the depot, who are called linehauls, and those that send goods to the depot, named backhauls. To each customer is associated an interval of time (time window), during which each one should be served. If a time window can be violated it is called soft, but this violation implies an additional cost. In this paper, only the upper limit of the interval can be exceeded. For solving this problem we created deterministic iterated local search algorithm, which was tested using a large set of benchmark problems taken from the literature. These computational tests have proven that this algorithm competes with best known algorithms in terms of the quality of the solutions andcomputing time. So far as we know, there is no published paper for this problem dealing with soft time windows, and, therefore, this comparison is only with the algorithms that do not allow time windows violation.